Effect of Body Size on Plasma and Tissue Pharmacokinetics of Danofloxacin in Rainbow Trout (Oncorhynchus mykiss) - Uney, Kamil; Corum, Duygu Durna; Marín, Pedro; Coskun, Devran; Terzi, Ertugrul; Badillo, Elena; Corum, Orhan (MDPI AG, 2024)
Danofloxacin is a fluoroquinolone antibiotic approved for use in fish. It can be used for bacterial infections in fish of all body sizes. However, physiological differences in fish depending on size may change the pharmacokinetics of danofloxacin and therefore its therapeutic efficacy. In this study, the change in the pharmacokinetics of danofloxacin in rainbow trout of various body sizes was revealed for the first time. The objective of this investigation was to compare the plasma and tissue pharmacokinetics of danofloxacin in rainbow trout of different body sizes. The study was conducted at 14 ± 0.5 °C in fish of small, medium, and large body size and danofloxacin was administered orally at a dose of 10 mg/kg. Concentrations of this antimicrobial in tissues and plasma were quantified by high performance liquid chromatography with ultraviolet detector. The plasma elimination half-life (t1/2ʎz), volume of distribution (Vdarea/F), total clearance (CL/F), peak concentration (Cmax), and area under the plasma concentration–time curve (AUC0–last) were 27.42 h, 4.65 L/kg, 0.12 L/h/kg, 2.53 µg/mL, and 82.46 h·µg/mL, respectively. Plasma t1/2ʎz, AUC0–last and Cmax increased concomitantly with trout growth, whereas CL/F and Vdarea/F decreased. Concentrations in liver, kidney, and muscle tissues were higher than in plasma. Cmax and AUC0–last were significantly higher in large sizes compared to small and medium sizes in all tissues. The scaling factor in small, medium, and large fish was 1.0 for bacteria with MIC thresholds of 0.57, 0.79, and 1.01 µg/mL, respectively. These results show that therapeutic efficacy increases with body size. However, since increases in danofloxacin concentration in tissues of large fish may affect withdrawal time, attention should be paid to the risk of tissue residue.
Keywords: aquaculture; QL1-991; Veterinary medicine; SF600-1100; body size related pharmacokinetics; HPLC; fluoroquinolones; Zoology; antibiotics; Article